PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, DAN RETURN ON ASSET TERHADAP PENYALURAN KREDIT PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Sri Suartini; Hari Sulistiyo; Hasna Fauzia (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
Bank is one of the financial institutions that have the main task as a financial intermediary institution. The Bank also provides other supporting services to support the smoothness of activities to collect and channel funds either directly or indirectly related to savings or credit activities. The increase in loans disbursed by commercial banks does not have continuity with the increase in credit growth, this is due to the supply or credit crunch phenomenon caused by many things such as the low quality of banking assets, the high non performing loan value or the drop in banking capital due to depreciation. The purpose of this research is to know whether there is influence of capital adequacy ratio, non performing loan, return on asset to credit distribution either partially or jointly. The method used in this research is descriptive verification method with quantitative approach which is sourced from annual financial statements of commercial bank and literature study. Sampling technique using non probability sampling with purposive sampling technique. The data obtained were analyzed by testing the validity of data, multiple linear regression analysis and hypothesis test using f test and t test. The results of this study indicate that partially capital adequacy ratio has a negative effect on credit distribution, non-performing loans have a positive effect on credit distribution and return on assets have a positive effect on credit distribution. While the joint capital adequacy ratio, non-performing loans, return on assets effect on credit distribution.